2018
DOI: 10.1177/0194599818815885
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Prevalence of Dysphagia among Patients Diagnosed with Unilateral Vocal Fold Immobility

Abstract: Objective To identify dysphagia prevalence and characteristics among patients with unilateral vocal fold immobility (UVFI) through a systematic review of current literature. Data Sources Embase, PubMed, ScienceDirect, Wiley Online Library. Review Methods Four electronic databases were reviewed according to the PRISMA criteria. Original English-language studies examining dysphagia among adult patients with UVFI met eligibility. Two researchers independently analyzed qualified articles. Results Of 227 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
(284 reference statements)
1
18
0
Order By: Relevance
“…The current study's operational definitions were developed to reflect variants of dysphagia studied in prior literature. Review of previous research on this topic identified a range of methods used to define the presence of dysphagia, including patient self‐report of symptoms, medical record documentation of signs and symptoms during clinical examination, administration of dysphagia questionnaires (e.g., DHI or EAT‐10), instrumental assessment (MBS/FEES), and PAS rates . Thus, this study's definitions included: Dysphagia symptoms were listed as the chief complaint for the clinic appointment.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The current study's operational definitions were developed to reflect variants of dysphagia studied in prior literature. Review of previous research on this topic identified a range of methods used to define the presence of dysphagia, including patient self‐report of symptoms, medical record documentation of signs and symptoms during clinical examination, administration of dysphagia questionnaires (e.g., DHI or EAT‐10), instrumental assessment (MBS/FEES), and PAS rates . Thus, this study's definitions included: Dysphagia symptoms were listed as the chief complaint for the clinic appointment.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this study's definitions included: Dysphagia symptoms were listed as the chief complaint for the clinic appointment. This definition only included patient‐reported symptoms An abnormal total score on a dysphagia self‐report questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations